2020
DOI: 10.3389/fnins.2020.594566
|View full text |Cite
|
Sign up to set email alerts
|

Is EEG Suitable for Marketing Research? A Systematic Review

Abstract: Background: In the past decade, marketing studies have greatly benefited from the adoption of neuroscience techniques to explore conscious and unconscious drivers of consumer behavior. Electroencephalography (EEG) is one of the most frequently applied neuroscientific techniques for marketing studies, thanks to its low cost and high temporal resolution.Objective: We present an overview of EEG applications in consumer neuroscience. The aim of this review is to facilitate future research and to highlight reliable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 89 publications
1
70
0
Order By: Relevance
“…This number was deemed appropriate to represent the sample since it is around the size of participants generally involved in this kind of study. This is confirmed by the review of Bazzani and colleagues [ 32 ], who reported that, over studies that used advertisings as stimuli, 33 was the average number of recruited participants. Five subgroups of subjects were randomly chosen 630 times (each n-th combination was different from the others) and the related outcomes were compared to the condition in which all the subjects were included.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This number was deemed appropriate to represent the sample since it is around the size of participants generally involved in this kind of study. This is confirmed by the review of Bazzani and colleagues [ 32 ], who reported that, over studies that used advertisings as stimuli, 33 was the average number of recruited participants. Five subgroups of subjects were randomly chosen 630 times (each n-th combination was different from the others) and the related outcomes were compared to the condition in which all the subjects were included.…”
Section: Discussionsupporting
confidence: 59%
“…The outcomes associated with the entire population were considered as reference since 36 is within the range of sample sizes generally involved in this kind of study. This number was deemed appropriate to assume the results were reliable, i.e., representative of the theorical population, in line with the scientific literature [ 32 ]. These subgroups were chosen since: (i) in the literature there is a large consensus considering [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] the optimal range of participants in neuroimaging studies [ 33 ]; (ii) in order to perform Analysis of Variance, the number of cases (i.e., 630) has to be much higher than the number of groups (i.e., five).…”
Section: Introductionmentioning
confidence: 99%
“…EEG is a non-invasive tool using electrodes on the scalp to record the frequency of the active neurons in the brain directly [78]. Additionally, EEG can record the activation regions in the brain in milliseconds due to the high temporal resolution, but on the opposite, has a poor spatial resolution that enables to record the cortical brain activity (approximately 1 cm3 brain structure) [70,74,[79][80][81]. According to literature, EEG has five frequency bands such as delta (0-4 Hz), theta (4-7 Hz), alpha (8-15 Hz), beta (16-31 Hz), and gamma (larger than 32 Hz) [46].…”
Section: Electroencephalography and Magnetoencephalographymentioning
confidence: 99%
“…This approach finds applications among different fields, such as neuromarketing, neuroeconomy, and neuromanagement. The application of neuroscience to these different disciplines, in particular to consumer neuroscience, allows researchers to delve into and apply neuroscientific tools to detect the decision-making process (Plassmann et al, 2012(Plassmann et al, , 2015Bazzani et al, 2020). This discipline investigates the antecedents and consequences of behavior, looks at the biological side, and even focuses on the information processing and functioning of attention, memory, and emotion (Yarkoni et al, 2011;Plassmann et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Neuroscience techniques, which are focused on forms of interpretations of reality based on cognitive schemes and experienced emotions and on the detection of decision-making process, can be used and applied in any communication exchange activating a reaction that can be detected (Plassmann et al, 2015;Cocco, 2016;Bazzani et al, 2020). This approach can also help the specific assessment process by measuring reactions useful for the choosing and meeting of organizational goals, detecting those elements related to engagement and stress, and supplying organizations with instruments to evaluate and conduct effective job interviews and, thus, meet their own organizational goals.…”
Section: Introductionmentioning
confidence: 99%